Snakes and Ladders Game for Early Childhood Cognitive Development - Mustakimah Mustakimah (Journal on Education, 2023)
This research is motivated by the application of education, which tends to be verbalistic and monotonous. Teachers tend to use classical education and less varied media so that learning can only partially stimulate cognitive development. This research aims to describe the process of implementing the snakes and ladders game to stimulate the cognitive growth of children aged 5-6 years in PAUD Kecamatan Gajah. This research uses qualitative research methods, as well as information-gathering methods using interviews, observation, and documentation. The sources of information are group B children and group B teachers. Checking the validity of the information uses the triangulation method. This research shows that implementing the Snakes and Ladders game in improving the cognitive abilities of children aged 5-6 years in PAUD in Gajah District has been going well. Therefore, teachers can use the implementation of the Snakes and Ladders game to stimulate cognitive development in early childhood.